Distance Learning Based on Human Literacy: An Alternative Learning to Foster Public Civility - Kusnadi Kusnadi (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2022)
The crisis of community identity reflects the neglect of the world of Education and culture to develop civic intelligence. Education emphasizes individual intelligence by ignoring efforts to link emotional intelligence diversity with collective citizenship intelligence. As a result, many people are unaware of their obligations and rights. In addition, many behaviors do not reflect politeness in society. Recently, blasphemy, insults, insults, and even threats are so easy to find in various places in public spaces. Therefore, civil intelligence education is the best solution for shaping public civility. Mental intelligence development is essential for a nation. It is necessary to develop literacy that can lead to a more noble and civilized life, namely human literacy. Human literacy is the estuary of data and technology literacy for 21st-century students for a more noble and civilized life. Distance Education has a significant role in building the quality of Education in Indonesia, especially in developing human literacy. The method used in the analysis of this discussion is a literature study. This article discusses civic intelligence as a challenge, distance education as a solution to the civic intelligence education process, the development of civic intelligence through human literacy, and the role of human literacy in shaping public civility in distance education.